Energy and exergy efficiency of water-based photovoltaic thermal (PVT) systems: an overview - Nurul Shahirah Binti Rukman; Ahmad Fudholi; Ivan Taslim; Merita Ayu Indrianti; Intan Noviantari Manyoe; Uce Lestari; Kamaruzzaman Sopian (Institute of Advanced Engineering and Science, 2019)
Conventional fuels are not free, scarce and expensive, and its future cost and availability are uncertain. Hence, the usage of solar energy in applications will probably increase and further become economically feasible in the near future. Solar energy is free, clean, and renewable and has been widely used in electricity generation and thermal energy via photovoltaic thermal (PVT) system. PVT is a hybrid system consists of a PV panel and a solar collector in a single unit to simultaneously produce electricity and thermal energy. In this review, energy and exergy efficiency for water-based PVT systems is presented. As conclusion, the study on exergy is still limited and is recommended to be furthered in order to obtained useful energy generation by the system.